Antisipasi Dampak negatif Penggunaan Smartphone Bagi Siswa kelas XI SMA Negeri 8 Batang Hari Melalui Layanan Bimbingan Kelompok - Iyut Mardiati (Jurnal Pendidikan Islam, 2020)
Abstract:Smartphones as a medium of communication bringconvenience to humans anywhere in the world to communicate, helpinghumans to shorten the mileage. No need to meet physically, but in theair can exchange information and deliver messages. In particularSmartphone technology is increasingly making human privacy soawake. If it is controlled, the smartphone certainly has a positiveimpact. However, if not, the facilities in the Smartphone can bemisused